2012
DOI: 10.9734/bjmmr/2012/1072
|View full text |Cite
|
Sign up to set email alerts
|

New Experimental Model of Brain Tumors in Brains of Adult Immunocompetent Rats

Abstract: Aims: Xenograft models, namely heterotransplantation of human cancer cells or tumor biopsies into immunodeficient rodents are the major preclinical approach for the development of novel cancer therapeutics. However, in these models the animals must be used only after the severe systemic immune suppression in order to ensure graft survival. Thus, additional new human brain tumor models without immune suppression of the recipient rodent may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…The results of this experiment demonstrated that human glioblastoma multiform cells induced as a xenograft in the brain of wild-type rats could successfully infiltrate in the host animal, considerably grew in size for two weeks, regress to nearly half the size of two weeks after four weeks, and completely regress after six weeks due to immunological reactions. Our observations are in agreement with the studies that reported the rejection of neural cells or brain tumor cells in xenograft models of animals ( Baklaushev et al, 2012 ; Barth & Kaur, 2009 ; Englund et al, 2002 ; Strojnik et al, 2006 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this experiment demonstrated that human glioblastoma multiform cells induced as a xenograft in the brain of wild-type rats could successfully infiltrate in the host animal, considerably grew in size for two weeks, regress to nearly half the size of two weeks after four weeks, and completely regress after six weeks due to immunological reactions. Our observations are in agreement with the studies that reported the rejection of neural cells or brain tumor cells in xenograft models of animals ( Baklaushev et al, 2012 ; Barth & Kaur, 2009 ; Englund et al, 2002 ; Strojnik et al, 2006 ).…”
Section: Discussionsupporting
confidence: 93%
“…This reaction induces a pattern of biological events including activation of the cellular immune system, activation of the humoral immune system, activation of endothelial cells, loss of vascular structure, hemorrhage, and edema. However, in the heterotransplantation model, the role and duration of immune system response in the process of tumor suppression are still unclear ( Halldén et al, 2003 ; Khalfoun et al, 2000 ; Ruggeri et al, 2014 ; Baklaushev et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…293 cells stably transfected with CHI3L1 have an accelerated growth rate relatively to the parental cells and can undergo anchorageindependent growth in soft agar that is one of the consistent indicators of oncogenic transformation [25,27]. Furthermore, 293_CHI3L1 cells implanted in the rat brain of adult immunocompetent animals have given rise to the large intracerebral tumors with the newly ingrown blood vessels [27,28].…”
Section: Immortalization and Transformation: The Central Role Of Karymentioning
confidence: 99%
“…There is also possibility to implant tumor cells taken directly from a patient diagnosed with tumor. In both approaches, immunodeficient and immunosuppressed rodents are usually used as experimental animals. , As there is no one model that ideally reflects the nature of a human brain tumor, different models have been verified in order to assess their usability in preclinical studies. …”
Section: Introductionmentioning
confidence: 99%